Emergent is Authentic: A Sociomaterial Perspective on Simulation-Enhanced Interprofessional Education. Issue 4 (2nd October 2017) - O'Brien, Bridget C.; Little, Judith Warren; Wamsley, Maria; Cook, Joseph G.; Yuan, Patrick; Rivera, Josette; Cianciolo, Anna T.; Dahlgren, Madeleine Abrandt; Ng, Stella L.; Stillsmoking, Kristina L.
ABSTRACT: This Conversations Starter article presents a selected research abstract from the 2017 Association of American Medical Colleges Western Region Group on Educational Affairs annual spring meeting. The abstract is paired with the integrative commentary of three experts who shared their thoughts stimulated by the study. The commentary explores the implications of sociomaterial perspectives for conceptualizing authenticity in the design and evaluation of simulation-enhanced interprofessional education.